Social, Economic and Political Implications of Nuclear Power Plant in Bangladesh - Karim, Ridoan; Karim , Md. Ershadul; Munir, Abu Bakar; Newaz, MD Shah (School of Social Sciences, USM, 2017)
Whether a global nuclear renaissance will usher or sustain, the affair hinges on a myriad of the socio-political and economic factors. In one hand, the consistent rise in the prices of oil, coal, fossil fuels and on the other, the lack of natural gas reserves has indicated the struggle of Bangladesh for energy demand, which is eventually going to persist in future. Consequently, due to the scarcity of oil and natural gas resource, nuclear energy surfaces as a palatable strategic option for Bangladesh’s future development agenda. However, a successful nuclear power program entails an extensive infrastructure. The control of nuclear energy is one of the prime concerns of science, industry, and politics. Henceforth, emancipating these issues, the paper will analyse the social and political implications regarding the incorporation of nuclear power plant in Bangladesh. The study of this paper is based on secondary sources where a qualitative research is conducted to analyse the socio, political and economic issues relating to the nuclear energy generation in Bangladesh. The study combines doctrinal and comparative socio-legal analysis. Consequently, one of the prime researches of the paper will skirt around the topic related to the public awareness and embroilment of such nuclear energy development in Bangladesh. The paper recommends Bangladesh to adopt a comprehensive energy law that should be realigned to consider noteworthy emphasis on sustainability, developing technical, financial and institutional constraints, and promoting public awareness and involvement associated with the generation of nuclear energy. Keywords: Reactor safety, Nuclear waste treatment, Nuclear Regulation,